Approximation of the classes $C^{ψ}_{β}H^{α}$ by biharmonic Poisson integrals - Abdullayev, F. G.; Kharkevych, Yu. I.; Абдуллаев, Ф. Г.; Харкевич, Ю. И.; Абдуллаєв, Ф. Г.; Харкевич, Ю. І. (Institute of Mathematics, NAS of Ukraine, 2020)
In the work we done the research of questions on approximation $(ψ,β)$-differentiable in the understanding of Stepanets functions that $(ψ, β)$-derivative belongs to the class $H^{α}$, by biharmonic Poisson integrals in uniform metric